Narcotics in Iceland: Security Issues and Prohibition Policy - Brynjólfur Sveinn Ívarsson 1987- (2012)
The aim of this thesis is to provide a brief overview of narcotics related security issues in Iceland. The security issues that are addressed are narcotics related criminal offenses, small arms proliferation, narcotics related collusion and police misconduct, money laundering, prescription forgery, the spread of pathogens among habitual drug users, the operation of motor vehicles under the influence of narcotics, and polluted narcotics. A second theme of the analysis is whether or not the official policy of drugs prohibition serves to amplify some or all of these security concerns. The findings of the thesis suggest that prohibition policy may serve to increase the motive for and/or scope of certain security concerns; especially insofar as it opens the way for further involvement of organized criminal syndicates. The analysis also suggests that Iceland has been until recently very ill equipped to deal with rising security concerns in this field, but that enforcement and the relevant legal framework have been growing more effective. However, at the same time it suggests that criminal syndicates have likewise become more professional.